Implementation of a Novel Near Visual Acuity Chart in an Emergency Department Setting. Issue 5 (September 2020) - Wu, James F.; Visotcky, Alexis; Szabo, Aniko; Eyler, Stephen; Siegmann, Peter; Griepentrog, Gregory J.; Warren, Clinton C.; Han, Dennis P.
ABSTRACT: Purpose: The quality of visual acuity (VA) measurement in emergency department (ED) settings can be affected by patient immobility and lack of standardized testing conditions. We implemented a previously validated, novel VA chart, the Runge Sloan letter near card, in a hospital ED and evaluated its impact on frequency and consistency of VA testing. Methods: Two hundred seventeen hospital ED ophthalmology consult records from December 1, 2016, to November 15, 2017, were evaluated in an IRB-approved protocol. Frequency of VA measurement and agreement between nonophthalmic ED technicians and ophthalmology physicians-in-training were assessed. Results: Implementation of the Runge card saw missed technician VA evaluations decrease from 36% (43/120) to 21% (20/97) of ophthalmic consults ( p = .01), without significant change in agreement of VA measurements. After implementation, the proportion of VA measurements differing between technicians and residents by ⩽2 lines was 51%; with pinhole testing, it improved to 64% ( p < .05). In patients with good VA of >20/80, pinhole increased agreement from 58% to 73% ( p < .05). Conclusions: Implementation of the Runge card was associated with improved frequency of VA measurement and, when combined with pinhole testing, increased agreement rates. Our findings suggest utility of training in the use of the Runge card in ED settings.